The Contemporary Significance Of Fakriddin Rozi And “Mafotihul Ghaib” - Abdurasul ABDULLAEV (Academia One, 2024)
the article focuses on the life and work of the famous Mufassir Fakhriddin Raza and his famous book “Mafatihul Gaiba”
Keywords: Kitаbut tafsir kabir; Kitаbut tafsir Sagir; Kitаbut tafsir Fatiha